Aggregation behaviour of hydrophobically modified poly(allylammonium) chloride - Tiera, M. J.; Tiera, VAD; de Toledo, E. C.; de Sena, G. L. (Springer, 2000)
The behaviour of hydrophobically modified poly(allylammonium) chloride having octyl, decyl, dodecyl and hexadecyl side chains has been studied in aqueous solution using fluorescence emission techniques. Micropolarity studies using the I-1/I-3 ratio of the vibronic bands of pyrene show that the formation of hydrophobic microdomains depends on both the length of the side chain and the polymer concentration. The I-1/I-3 ratio of the polymers with low hydrophobe content (less than 5% mel) changes substantially when reaching a certain concentration. These changes are assigned to aggregation originating from interchain interactions. This behaviour is also confirmed by the behaviour of the monomer/excimer emission intensities of pyrene- dodecanoic acid used as a probe. For polymers having dodecyl side chains and hydrophobe contents higher than 10%, aggregates are formed independently of the polymer concentration. Anisotropy measurements show that microdomains resulting from the inter- and/or intramolecular interactions are similar to those observed for cationic surfactants. Viscosity measurements show that the coil dimensions are substantially decreased for the polymers having high hydrophobe contents, indicating intramolecular associations.
Keywords: cationic amphiphilic polymers; aggregation; pyrene fluorescence spectroscopy; hydrophobic microdomains